2015
DOI: 10.1590/1807-3107bor-2015.vol29.0060
|View full text |Cite
|
Sign up to set email alerts
|

Changes in irradiance and energy density in relation to different curing distances

Abstract: The present study aimed to assess the influence of curing distance on the loss of irradiance and power density of four curing light devices. The behavior in terms of power density of four different dental curing devices was analyzed (Valo, Elipar 2, Radii-Cal, and Optilux-401) using three different distances of photopolymerization (0 mm, 4 mm, and 8 mm). All devices had their power density measured using a MARC simulator. Ten measurements were made per device at each distance. The total amount of energy delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“…During the past decade, resin-based composite has become the most commonly used restorative material worldwide due to its aesthetic and adhesive properties. Clinically, these materials require careful attention to the presence and/or risk of salivary contamination, proper removal of solvents [26,27] and power energy for proper polymerization [28]. While composites have relatively good adhesive or sealing properties, polymerization shrinkage of the resin during curing combined with cyclic occlusal loading may impose internal stresses [29].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, resin-based composite has become the most commonly used restorative material worldwide due to its aesthetic and adhesive properties. Clinically, these materials require careful attention to the presence and/or risk of salivary contamination, proper removal of solvents [26,27] and power energy for proper polymerization [28]. While composites have relatively good adhesive or sealing properties, polymerization shrinkage of the resin during curing combined with cyclic occlusal loading may impose internal stresses [29].…”
Section: Discussionmentioning
confidence: 99%
“…Given that dentists wish to reduce the time spent light curing, this value was considered to be the minimum irradiance necessary to adequately polymerize a 2 mm increment of composite (20,21). Six LCUs delivered inadequate irradiance in posterior region: KON-LUX, Altlux II, Biolux Standard, TL-01, Optilux 501, DX Turbo LED 1200.…”
Section: Characteristics Of Light Curing Units Used Inmentioning
confidence: 99%
“…The concept of total energy demonstrates that the photopolymerization process depends on the energy taken up by the resin, in which irradiance is multiplied by exposure time (15). Previous studies have argued that irradiance should range from 6 to 16 J/cm 2 to be effective, but these values are not absolute as they depend on other factors such as type, thickness, and translucency of the resin and on the type of photoinitiator (11,15). In the present study, exposure to radiation was 9.6 J/cm² for light activation with VALO Ortho Cordless and 48 J/cm² for light activation with Optilight Max.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the findings of the present study, some studies have suggested that the extremely thin layer of resin with no need for deep light activation used for bracket bonding would cancel out the effect associated with the difference in energy uptake, which, by itself, would not be enough to change SBS. In addition, the wavelengths of LED devices would efficiently stimulate camphorquinone, rendering photopolymerization effective, regardless of the difference in energy uptake (4,11).…”
Section: Discussionmentioning
confidence: 99%